Coffee Under Pressure - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: Vulnerability of farmers equals vulnerability of supply chain. Inclusive management involves those that contribute to growing, selling and changing strategies. Crop modelling under different climate conditions requires knowledge of who’s growing, selling and involved in the supply chain. It also requires an analysis of who the beneficiaries of the value chain are and who will be adversely affected by changes in climate and in practice in order to identify appropriate adaptation strategies. Gender analysis is critical.